«Gründrisse einer öekonometrie» – економетрична бухгалтерська теорія, розроблена в Галичині на рубежі ХІХ–ХХ ст. - Лемішовська, О. С.; Lemishovska, O. S. (Видавництво Львівської політехніки, 2005)
Проведено змістовну оцінку розробленої на території Галичини економетричної бухгалтерської теорії. Розкрито її спрямованість, параметри формулювання та функціональне призначення. Проведено порівняльний аналіз принципів побудови з виділенням проблемних аспектів сучасного економетричного моделювання. Визначено недоліки та сильні сторони до використання для сучасної облікової науки.

The content and subject orientation of accounting (balance) econometric theory are revealed, the level of substantiation of its use of macroeconomic approaches and mathematical apparatus as auxiliary means for increasing the reliability of quantitative measurement (quantification) of property and capital actually existing at a separate enterprise is assessed. The parameters and conceptual and methodological orientation of this development, presented by a new system of measuring values in the economy on the basis of accounting information, are studied. The level of argumentation of selection in the accounting system of additional tools for the development of the theoretical basis of accounting is analyzed and the possibilities of their practical application are evaluated. The results of comparative analysis of the basic principles of the studied theoretical development with the principles and content of building the basic foundations of "traditional" econometrics with the allocation of problematic aspects in the methods of econometric modeling. The hypothesis of the study is the assumption of the development in the study work of individual ideas that can be rationally used for the development of modern accounting and econometric paradigms. The research concept is constructed as follows: in the first part the generalized comparative analysis of bases and principles of construction of econometric concepts is carried out. The second part of this historical-accounting and interdisciplinary research reveals a panorama of the then institutional environment of Austro-Hungarian Galicia at the turn of the century, whose activities influenced the development of the theoretical principles of accounting in this development. The third part of the research presents the results of critical analysis and evaluation of methodological and methodological approaches to the display of objects of accounting and reporting, the possibility of using mathematical modeling tools in practical accounting. The methodological principles of the research are based on the general scientific principles of historical knowledge and critical comprehension of the studied material, which together with the application of the comparative-historical method allowed to reveal the scientific value of the studied development. The possibility and expediency of using certain aspects of the studied development for the modern development of accounting and econometric science are determined and substantiated.
«Gründrisse einer öekonometrie» – econometric accounting theory developed in Galicia at the border of the XIX-XX century
Keywords: бухгалтерська теорія; економетрія; економографія; майно; капітал; акомодація; економетричні рівняння; квадрига і октагон; бухгалтерський баланс; accounting theory; econometrics; economography; property; capital; accommodation; econometric equations; quadriga and octagon; balance sheet; 657.1; 930.001.92; 316.177; 377(091)